MARGARITA JOVER, ALEX WALL - Ecologies of Prosperity for the living city - Monclús , Javier (ZARCH, 2021)
Margarita Jover, Alex WallEcologies of Prosperity for the living city Virginia: AR+D Applied Research + Design Publishing. University of Virginia School of Architecture, 2019. 350 p. Idioma: inglés. Tapa blanda. 40 $ISBN: 978-1-940743-50-9